(22-2x)(14-2x)(x)=

Simple and best practice solution for (22-2x)(14-2x)(x)= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (22-2x)(14-2x)(x)= equation:


Simplifying
(22 + -2x)(14 + -2x)(x) = 0

Reorder the terms for easier multiplication:
x(22 + -2x)(14 + -2x) = 0

Multiply (22 + -2x) * (14 + -2x)
x(22(14 + -2x) + -2x * (14 + -2x)) = 0
x((14 * 22 + -2x * 22) + -2x * (14 + -2x)) = 0
x((308 + -44x) + -2x * (14 + -2x)) = 0
x(308 + -44x + (14 * -2x + -2x * -2x)) = 0
x(308 + -44x + (-28x + 4x2)) = 0

Combine like terms: -44x + -28x = -72x
x(308 + -72x + 4x2) = 0
(308 * x + -72x * x + 4x2 * x) = 0
(308x + -72x2 + 4x3) = 0

Solving
308x + -72x2 + 4x3 = 0

Solving for variable 'x'.

Factor out the Greatest Common Factor (GCF), '4x'.
4x(77 + -18x + x2) = 0

Factor a trinomial.
4x((7 + -1x)(11 + -1x)) = 0

Ignore the factor 4.

Subproblem 1

Set the factor 'x' equal to zero and attempt to solve: Simplifying x = 0 Solving x = 0 Move all terms containing x to the left, all other terms to the right. Simplifying x = 0

Subproblem 2

Set the factor '(7 + -1x)' equal to zero and attempt to solve: Simplifying 7 + -1x = 0 Solving 7 + -1x = 0 Move all terms containing x to the left, all other terms to the right. Add '-7' to each side of the equation. 7 + -7 + -1x = 0 + -7 Combine like terms: 7 + -7 = 0 0 + -1x = 0 + -7 -1x = 0 + -7 Combine like terms: 0 + -7 = -7 -1x = -7 Divide each side by '-1'. x = 7 Simplifying x = 7

Subproblem 3

Set the factor '(11 + -1x)' equal to zero and attempt to solve: Simplifying 11 + -1x = 0 Solving 11 + -1x = 0 Move all terms containing x to the left, all other terms to the right. Add '-11' to each side of the equation. 11 + -11 + -1x = 0 + -11 Combine like terms: 11 + -11 = 0 0 + -1x = 0 + -11 -1x = 0 + -11 Combine like terms: 0 + -11 = -11 -1x = -11 Divide each side by '-1'. x = 11 Simplifying x = 11

Solution

x = {0, 7, 11}

See similar equations:

| 20w-18w+6w+1=9 | | 7g+6=g-6 | | x(4)=20 | | 9r+r+r-7r=16 | | 6m-6m+m+3m+2=10 | | 2k-2k+6k-5=13 | | (x(5x^3)^-2)/(x^-4) | | 4b-2b-2b+b-1=17 | | 5q-6=3-49 | | 9(6x+6)=5 | | 4k-3=39-2k | | 9.6(4x-4)=6 | | http://i.imgur.com/AztDgzf.png | | 2006-258x=8328 | | T-7=6 | | 5x/9=3x/4-7 | | 3x-4=-50 | | 3/2x-7=x-5 | | 2(2x+2)=22 | | 4(-2x+3)=116 | | x+2(x+3)=3(x+2) | | X-64y^3=0 | | -3x+4=-36 | | 0=-5U-37 | | 2(x-4)-15=27 | | 3+w=-2 | | 1.2(x+5)=.5x-1 | | 2(x+4)=-3(2x-1) | | 8/24-1/9 | | 0.42/4.41 | | 4x+10=10x+7 | | 3x^3-35x^2+122x-120=0 |

Equations solver categories